Nature Potential and Micro, Small, Medium Entreprise (MSMES) In the Development of Ecotourism Areas in Gombengsari Village, Kalipuro District, Banyuwangi Regency - Sugiarto; Ertien Rining Nawangsari (Future Science)
Gombengsari Village is one of the tourist areas in Banyuwangi Regency, many tourist area and MSME in the Gombengsari District, but still cannot be search using the Google Map application. Utilization of Information Technology today is a process of community empowerment in strengthening the community to master technology and information. The development of technology Geographic Information System is expected to improve the performance of an organization or agencies to be more effective and efficient information as well as easy in receipt of things to say in this case is performance pokdarwis in gombengsari village. Spatial data this is what found focus group disscussion from residents and pokdarwis, produces maps of thematic KML data, and export to jpg, which can be used for Static Maps. Spatial data has reached 93% of the 5 Environment in the Gombengsari Kelurahan that have been understood by the Gombengsari POKDARWIS, which will then be socialized to the community, how important it is to live in ecotourism.